Financial Performance and Market Share in Indonesia Islamic Banking: Stakeholder Theory Perspective - Aminah, Aminah; Soewito, Soewito; Erina, Nuria; Khairudin, Khairudin; Damayanti, Tri (Opción, 2019)
This research aimed to examine the influence of financial performance on market share in Indonesia Islamic Banking. We use return on assets (ROA), capital adequacy ratio (CAR), non performing loan (NPL), operating expens- es-operating income (OEOI/BOPO), and financing to deposit ratio (FDR) as proxies of financial performance. Also, we apply market share as the compari- son of Islamic banking total asset on total asset of Indonesia banks. This study is using stakeholder perspective analysis. How market share is influenced by financial performance, since market share is the reflection of stakeholders perception. We collect 33 Islamic Banks financial report in 2013-2015 using times series model. The result shows that ROA has positive significant effect on market share. Meanwhile, NPL and BOPO have negative significant effect on market share. Otherwise, FDR has no significant effect on market share. Based on the research findings, this study confirms that in Indonesia Islamic banking pro- vides goodnews in their financial performance.